The articulation between the IACHR and the Peruvian Constitution of 1993: restrictive rules of the New Constitutional Procedural Code - Neyra Zegarra, Ana (2025)
This text critically analyzes Peru’s new Constitutional Procedural Code in light of the standards of the Inter-American Human Rights System, particularly regarding effective judicial protection, due process, and the principle of conventionality control.Through a pluralistic dialogue among different doctrinal positions, it examines key reforms such as the transfer of jurisdiction over habeas corpus, the regulation of preliminary dismissals, the express omission of collective amparo proceedings, and the restrictions introduced on the use of Inter-American Court jurisprudence. The analysis highlights the tensions between the pursuit of procedural efficiency and the requirement to guarantee real, timely, and effective access to constitutional justice, in accordance with Articles 8 and 25 of the American Convention on Human Rights.